A Blumgart Anastomosis-Based Half-Invagination Pancreaticoenterostomy with Better Applicability to Laparoscopy and Lower Incidence of Pancreatic Leakage. (23rd February 2023) - Sun, Qiang; Peng, Peng; Gong, Xueyi; Wu, Jianlong; Zhang, Qiao; Hu, Zhipeng; Chang, Xiaojian; Hu, Zemin
Abstract : Background . The Blumgart anastomosis (BA) is one of the safest anastomoses for pancreatic stump reconstruction. The incidence of postoperative pancreatic fistula (POPF) and postoperative complications is low. However, how to make laparoscopic pancreaticoenterostomy easier and safer is still a topic to be discussed. Methods . The data of patients who underwent laparoscopic pancreaticoduodenectomy (PD) from April 2014 to December 2019 were analyzed retrospectively. Results . Half-invagination anastomosis was performed in 20 cases (HI group), and the Cattell-Warren anastomosis was carried out in 26 cases (CW group). The amount of intraoperative bleeding, operation time, and postoperative catheterization time in the HI group was significantly less than those in the CW group. Besides, the number of patients at the Clavien-Dindo grade III and above in the HI group was significantly less than that in the control group. Moreover, the incidence of POPF in the HI group was significantly lower than that in the CW group. Furthermore, fistula risk score (FRS) analysis showed that there was no high-risk group, and the highest risk in the medium-risk group was pancreatic leakage. In addition, the incidence of pancreatic leakage in the HI group and CW group was 7.7% and 46.67%, respectively, while the incidence of pancreatic leakage in the HI group was significantly lower than that in the CW group. Conclusions . The half-invagination pancreaticoenterostomy based on the Blumgart anastomosis should have good applicability under laparoscopy and could effectively reduce the incidence of postoperative pancreatic leakage.